Peran Supervisi Kepala Madrasah dalam Meningkatkan Mutu Pendidikan di MTs Negeri Kulon Progo - Legiman (Jurnal Pendidikan Madrasah, 2019)
This research aims to determine the role of the head of Madrasah in improving the quality of education in MTs Negeri 4 Kulon Progo, and to help improve the competency of teachers in the learning activities with a real, measurable, controlled, directional program to achieve learning objectives. This research uses qualitative descriptive methods with data collection through observation, interviews and documentation. The results of this research are: 1) supervision of the head of the district of the state of the principal of the school 4 Kulon Progo includes education, managerial, administrator, supervisor, leader, innovator, and motivator; 2) The role of quality improvement is done by increasing the professionalism of teachers by giving opportunities to teachers; 3) Factors affecting the implementation of the head of the Madrasah include: the planning, implementation and follow-up that is carried out continuously to the teachers and education personnel.